Posisi Perempuan Papua dalam Cerita Rakyat Papua - Asmabuasappe Asmabuasappe (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Papua women has duties on family and custom. They must do the heavy duties and they also get the physically violence from their husband. They lives on depression, but they have larger dominance. The dominance born from the weakness and depression. Woman as family beginning has get confession that shown in Papua folklores. Description of women position on folklores use literary sociology and feminism with deconstruction method. This analysis shown the women has the big duty on their family and community.